AI-DRIVEN CAPITAL ASSET PRICING MODEL FOR ENHANCING SHARIAH-COMPLIANT INVESTMENT DECISIONS – A CHINESE STOCK MARKET ANALYSIS - Katterbauer, Klemens; Syed, Hassan; Cleenewerck, Laurent; Genc, Sema Yilmaz (International Journal of Islamic Business & Management, 2023)
The CAPM makes it possible to estimate prices for specific instruments, like stocks, to project investment returns. As a key element of corporate finance and investment banking, the CAPM investigates the relationship between the level of risk associated with the investment and the inherent risks of the market as a whole. Several assumptions must be used to create the AI-driven mathematical model for Islamic financial assets to achieve the model. The first is that the expected values and standard deviations of the asset’s returns are the only factors that influence investors’ choices. Additionally, since the zakat and purification are deducted from the anticipated returns, there are no transaction fees. The assets may be marketable and are infinitely divisible in addition. Finally, there is no cap on the amount that may be lent or borrowed at the Sukuk profit rate or other Islamic benchmark rates because all expectations are homogenous. We presented a new AI-driven Islamic CAPM for the estimation of returns for Shariah-compliant A-Shares enterprises. The methodology represents a new AI-driven estimation framework integrated into the Islamic CAPM methodology for the estimation of returns and selection. The methodology was evaluated on an Islamic A-share portfolio, with the stocks being listed on both the Shenzhen and Shanghai stock exchanges. The analysis demonstrates the ability of the methodology to provide Shariah-compliant optimal returns for the stocks and ensure Shariah compliance of the portfolio allocations. JEL Classification Codes: K22, L11, O11, C61, C68.